Transformation of the political struggle model at the village level due to the fight for village fund resources: A case study of village head elections before and after the enactment of UU Desa Number 6 of 2014 - Jafar Ahmad; Heri Herdiawanto; Laode Harjudin (Masyarakat, Kebudayaan dan Politik, 2023)
This study captures how the Village Law (UU) Number 6 of 2014 has radically changed political behavior at the village level. The political dynamics involved several former DPRD members, former KPU members, and local businessmen in the succession arena for the Village Head Election (Pilkades), in which conditions were rarely encountered in previous times. This study analyzed how changes occurred as they were triggered by the struggle for resources due to the allocation of village funds (DD). This study uses qualitative research methods. Data were collected through interviews with actors who contested in village elections, documentation, and literature studies. The results of this study show how changes in political behavior at the village level only occur after the Village Law is enacted. This study concludes that the Village Law number 6 of 2014 has shifted the political behavior of rural communities as evidenced by the massive circulation of money politics which has led to tense political battles. This study also concludes that the Village Law entices political actors and local businessmen to participate in the contest to seize the power of the village head.